Government mainstreaming of agri-nutrition messaging reached over 99,000 Kenyan children aged 0-23 months for improved dietary consumption - CGIAR Research Program on Livestock (2021)
The ILRI Accelerated Value Chain Development (AVCD) program nutrition component collaborated with the Kenya government to develop agri-nutrition community dialogue cards as part of a social behaviour change communication activity aimed at improving nutrition practices for children below 2 years of age and Women of Reproductive Age (WRA). By 2021, over 99,000 children 0-23 months were reached with nutrition messaging using the cards, which are now being rolled out by the Ministry and used outside of AVCD sites.